Constraint-based Learning of Phonological Processes - Barke, Shraddha; Kunkel, Rose; Polikarpova, Nadia; Meinhardt, Eric; Baković, Eric; Bergen, Leon (2019 Empirical Methods in Natural Language Processing, 2019)
Phonological processes are context-dependent sound changes in natural languages. We present an unsupervised approach to learning human-readable descriptions of phonological processes from collections of related utterances. Our approach builds upon a technique from the programming languages community called constraint-based program synthesis. We contribute a novel encoding of the learning problem into Boolean Satisfiability constraints, which enables both data efficiency and fast inference. We evaluate our system on textbook phonology problems and datasets from the literature and show that it achieves high accuracy at interactive speeds.